2018
DOI: 10.1177/1457496918783725
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern of Defects in Mesorectal Specimens: Is There a Difference between Transanal and Laparoscopic Approaches?

Abstract: The ratio of defects below the peritoneal reflection was lower in the transanal total mesorectal excision group. Whether this is due to a lower incidence of defect in transanal total mesorectal excision is not part of our study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…A total of 12 studies [ 24 25 26 27 28 30 31 32 34 35 36 38 ] reported operation time in 946 patients, and we found no statistically significant difference between TaTME and LaTME groups (MD, 7.52; 95% CI, −10.03–25.07; P = 0.400) ( Fig. 2A ).…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations
“…A total of 12 studies [ 24 25 26 27 28 30 31 32 34 35 36 38 ] reported operation time in 946 patients, and we found no statistically significant difference between TaTME and LaTME groups (MD, 7.52; 95% CI, −10.03–25.07; P = 0.400) ( Fig. 2A ).…”
Section: Resultsmentioning
confidence: 72%
“…Finally, 16 cohort studies met all the inclusion criteria and none of the exclusion criteria ( Fig. 1 ) [ 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 ]. Seven of the cohort studies were case-matched studies comparing TaTME with LaTME for rectal cancer [ 25 28 29 30 31 36 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially for patients with ultra-low rectal cancer or who intend to undergo intersphincteric resection, the rectal wall is incised through the anus, and then the space of internal and external sphincter is expanded and separated upward, the mesorectum can be completely removed. Perdawood et al [24] compared the mesorectal resection quality of rectal cancer, especially for tumors below the peritoneal reflex after TaTME and LaTME. It Fig.…”
Section: Discussionmentioning
confidence: 99%